Advancements in Accident Tolerance Fuel: A New Horizon in Nuclear Safety - Ngarayana, I Wayan; Kurniawan, Rusbani; Rachman, Agus Nur; Nugraha, Eka Djatnika; Ekaranti, Egnes; Andani, Ika Wahyu Setya (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2026)
Accident Tolerant Fuels (ATFs) are a breakthrough in nuclear safety that can reduce the hazards of nuclear reactor accidents by preventing core meltdowns and withstanding extreme conditions. This paper provides a comprehensive overview of the development and current state of ATF technology, tracing its evolution and highlighting key technological milestones. We used different case studies to assess how ATFs work and perform in actual situations. Despite the promising capabilities of ATFs, they face difficulties in their development and deployment. We delve into the technical, regulatory, and economic hurdles that must be overcome to realize the full potential of ATFs. Looking ahead, we explore the prospects of ATFs, discussing potential advancements and their implications for the nuclear industry. The findings of this paper underscore the transformative role of ATFs in enhancing nuclear reactor safety and charting a new horizon in nuclear technology.